Strategi Adaptasi Bermukim dalam Merespon Banjir Rob di Tambak Lorok, Semarang - Lukman Hendra Septian; Agustinus Adib Abadi; Allis Nurdini (RUAS, 2022)
Various adaptation strategy efforts have been made to reduce the impact due to the risk of environmental changes. Tidal flooding in the coastal area of Semarang is predicted to increase. Settlements affected by tidal flooding need to anticipate to reduce the risk of greater losses. The Tambak Lorok settlement is a phenomenon of resilience to live in a tidal flood disaster area. The purpose of this study is to explain the adaptation strategy of accommodation to settle in coastal areas affected by tidal floods in Tambak Lorok, Semarang with a qualitative descriptive approach. Data collection was carried out using a simple random sampling method with a questionnaire on 100 respondents of the Tambak Lorok community in 5 RW. The collected data are processed and interpreted by the methods of percentage description analysis and correlation analysis. It was concluded that the accommodation adaptation strategy for the Tambak Lorok community in responding to tidal flood disasters is influenced by factors of length of residence, monthly income, number of family members, perceptions of disasters, responses that have been carried out, regulations, and disaster characteristics. Adaptation to the adjustment is carried out by elevating the ground floor and increasing the height of the building structure. Behavioral adaptation is carried out by arranging the location of goods, and most people do not have a relocation plan.